Review of Notacanthella Jacobus & McCafferty, 2008 (Ephemeroptera: Ephemerellidae) in Thailand, with the redescription of Notacanthella commodema (Allen, 1971) - Auychinda, Chonlakran; Sartori, Michel; Boonsoong, Boonsatien (Zootaxa, 2020)
Larvae of the Notacanthella Jacobus & McCafferty, 2008 species N. commodema (Allen, 1971) and N. quadrata (Kluge & Zhou, 2004) from Thailand are compared and redescribed. Both species have serrations on maxillary canines, as does N. perculta (Allen, 1971) from Vietnam, and this contributes to synonymizing the subgenus Samiocca Jacobus & McCafferty, 2008 under Notacanthella s.s. (= Samiocca n. syn.). The Thailand species can be differentiated by the numbers of thoracic and abdominal tubercles. In addition, the chorionic structure of N. quadrata is investigated for the first time by scanning electron microscopic technique.